Use of the Sports Performance Index for Hockey (SPI-H) to predict NHL player value - Tarter, B.; Kirisci, L.; Tarter, R.; Jamnik, V.; Gledhill, N.; McGuire, E. J. (International Journal of Performance Analysis in Sport, 2009)
Elite junior hockey players (N=3,675) ranked by Central Scouting Service of the National Hockey League (NHL) prior to the NHL Entry Draft between 1993-2002 were studied to determine whether it is possible to predict their "value" to the team five years later. Using the Sports Performance Index for Hockey (SPI-H), it was found that time on ice (an indicator of the coach's desire to play the individual) and number of times the athlete was selected as one of the "Three Stars" of the game could be accurately predicted for forwards and defensemen five years after the Entry Draft. These results indicate that it is feasible to predict, prior to the team's selection of players, the athlete's long-term value to the team.